Factors influencing value added tax (VAT) compliance intention among SMEs in Nigeria - Gimba, Hannatu Yohanna (2018)
The contribution of Value Added Tax (VAT) to the total revenue of Nigeria remains consistently low and is relatively decreasing due to low compliance by the Small and Medium Enterprises (SMEs). Prior studies gave more attention to income tax compliance than VAT compliance; however, VAT is ranked as the most non-remittance tax in recent times. Considering all the factors that can influence VAT compliance are numerous but just a few would adhere specifically to Nigeria which are discussed in this study. Thus, this study investigates empirically the factors influencing VAT compliance intention among SMEs in Nigeria. In order to gain in-depth understanding of the phenomenon, the study incorporates detection probability, penalty magnitude, SME reputation, fairness in the tax system and mental tax accounting into the Theory of Planned Behavior (TPB). The study was designed using SMEs survey method. Cluster random sampling technique was applied to select the samples of the study from the six industrial areas in Kano state, Nigeria. The primary data were collected through self-administered questionnaire, which were treated statistically using multiple regression analysis and other statistical techniques.The results reveal that SMEs’ perception about subjective norms, perceived behavioral control, detection probability, SME reputation and fairness in the tax system are positively significant to VAT compliance intention. However, attitude towards VAT compliance, penalty magnitude and mental tax accounting are not related to VAT compliance intention among SMEs in Nigeria. By implication, the findings of the study suggests that policy makers should map-out strategies to improve the quality of services through fairness in the tax system, publishing the names of defaulting SMEs and improving their performance on detection. Furthermore, policies should be directed towards strengthening these factors to reawaken the culture of VAT compliance among SMEs in Nigeria.